Kashmir: the forgotten conflict. (October 2014) - Geelani, Gowhar
The author, a Kashmiri journalist, contemplates how Kashmir is being publicly portrayed. Though atrocities like the Holocaust are quite rightly memorialised for their horror, the world ignores the Kashmir conflict despite its 80, 000 dead, 6, 000 mass and unmarked graves, and thousands of disappeared youth – post resistance of 1989. And while provocations like the execution of Mohammad Afzal Guru and other oppressive tactics by India are still radicalising new sections of Kashmiri youth, India publicly promotes the notion of a Kashmir at peace whilst never accepting its role in human rights abuses. Who, asks the author, will tell Kashmir's story? Who will memorialise the atrocities it has suffered?